Impedance network-based ultra sparse matrix converter with enhanced voltage gain - Hassan, Zahid; Khan, M. A.; Islam, Md. Rabiul (International Journal of Power Electronics and Drive Systems (IJPEDS), 2024)
The matrix converter is devised to achieve sinusoidal input current and output voltage, and high power density. The typical matrix converter gives voltage gain less than unity using a significantly large number of switches. To reduce the number of switches an ultra sparse matrix converter (USMC) is introduced whose voltage gain is still less than unity. Researchers also introduced many modified versions of these matrix converters including quasi-Z-source, series Zsource, switched inductor, and switched capacitor USMCs. Although all of these matrix converters have their relative advantages and disadvantages in terms of the number of switches and passive elements, the voltage gain is still marginal. This paper focused on achieving higher voltage gain using minimal switches and passive elements. We proposed a doubler boost impedance network based ultra sparse matrix converter (DB-USMC). The doubler boost impedance network consists of a boost stage and doubler stage where the boost stage enhances the voltage and the doubler stage makes it double. The voltage gain of the proposed DB-USMC converter is 4.00 at a 50% duty cycle. The obtained results of the proposed DB-USMC converter show a path to get superior voltage gain using minimal switches and passive elements in a cost-effective manner.